Role of the tonsil-oropharynx ratio on lateral cephalograms in assessing tonsillar hypertrophy in children seeking orthodontic treatment - Chenxing Lv; Liu Yang; Peter Ngan; Wenjie Xiao; Tingting Zhao; Bojun Tang; Xiong Chen; Hong He (BMC, 2023)
Abstract Objectives To analyze the diagnostic value of the tonsil-oropharynx (T/O) ratio on lateral cephalograms for evaluating tonsillar hypertrophy (TH). Methods A cross-sectional study was performed on 185 consecutive children (101 males, 84 females; mean age 7.3 ± 1.4 years) seeking orthodontic treatment. The T/O ratios on lateral cephalograms were calculated following Baroni et al.'s method. Tonsil sizes were clinically determined according to the Brodsky grading scale. Spearman correlation coefficients between the T/O ratio and clinical tonsil size were calculated with the total sample and subgroups and then compared between subgroups. Diagnostic value was analyzed using the receiver operating characteristic (ROC) curve, sensitivity, specificity, positive and negative predictive values, and accuracy. Results There was a strong correlation between the T/O ratio and clinical tonsil size in children (ρ = 0.73; P < 0.001). A significantly higher correlation coefficient was found in the Class III children. The ROC curve revealed an area under the curve of 0.90 (95% CI, 0.86-0.94; P < 0.001). The optimal cutoff value of the T/O ratio for predicting TH was 0.58, with a sensitivity of 98.7% and specificity of 64.2%. Employing the cutoff value of 0.5, the sensitivity was 100% and the specificity was 45.9%. Conclusions Measurement of the T/O ratio on lateral cephalograms may be helpful to initial screening in children for TH. Practitioners may combine the clinical examination of tonsil size with the cephalometric findings for a more comprehensive evaluation.